2022
DOI: 10.1002/nop2.1521
|View full text |Cite
|
Sign up to set email alerts
|

Shift work disorder, mental health and burnout among nurses: A cross‐sectional study

Abstract: Aim:The aim of the study was to examine the relationships among nurses' shift work disorder, mental health and burnout to inform efforts to alleviate shift work disorder.Design: This cross-sectional study was conducted in China using a web-based platform for questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…(19) Beberapa penelitian melaporkan bahwa perawat berisiko tinggi dengan gangguan kerja shift memiliki risiko yang jauh lebih tinggi untuk mengalami masalah kesehatan mental dan kelelahan. (20)(21)(22) Penelitian ini memiliki beberapa kelemahan seperti kurang sempurnya teknik wawancara, karena peneliti masih pemula sehingga memiliki keterbatasan dalam hal kemampuan dan keterampilan, yang mungkin akan berdampak pada kelengkapan data.…”
Section: Pembahasanunclassified
“…(19) Beberapa penelitian melaporkan bahwa perawat berisiko tinggi dengan gangguan kerja shift memiliki risiko yang jauh lebih tinggi untuk mengalami masalah kesehatan mental dan kelelahan. (20)(21)(22) Penelitian ini memiliki beberapa kelemahan seperti kurang sempurnya teknik wawancara, karena peneliti masih pemula sehingga memiliki keterbatasan dalam hal kemampuan dan keterampilan, yang mungkin akan berdampak pada kelengkapan data.…”
Section: Pembahasanunclassified
“…The long-term irregular work pattern tends to disrupt the physiological rhythm of individuals, leading to burnout, emotional disorders, and even various physical and mental illnesses (Imes et al, 2023;Matheson et al, 2014). A recent cross-sectional study from China demonstrated that about 60% of shift nurses exhibited work-related disorders, manifesting as a higher incidence of mental health problems, sleep disorders, and burnout (Cheng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The long‐term irregular work pattern tends to disrupt the physiological rhythm of individuals, leading to burnout, emotional disorders, and even various physical and mental illnesses (Imes et al., 2023 ; Matheson et al., 2014 ). A recent cross‐sectional study from China demonstrated that about 60% of shift nurses exhibited work‐related disorders, manifesting as a higher incidence of mental health problems, sleep disorders, and burnout (Cheng et al., 2023 ). Moreover, long‐term shift work was identified to be a significant risk factor for various serious disorders, such as mental disorders (Booker et al., 2020 ), dementia (Ling et al., 2023 ), endocrine disorders (Hansen et al., 2016 ), and cardiovascular diseases (Vetter et al., 2016 ), especially for the females.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Suffering from mental health issues not only affects nurses' health, but also directly contributes to their burnout. 4 Reduced personal accomplishment, emotional exhaustion, losing a positive outlook toward clients, or depersonalization are all signs of burnout. 5 Therefore, the emergence of burnout has a decidedly negative impact on the workforce and quality of healthcare, including workforce turnover, increased medical errors, and decreased patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%